AQ-8 Detection of the Foot and Mouth Disease in Buffalo Meat Originating From India with the Reverse-Transcription PCR Method - Hestu Prastanti; . Marjono; Melyna Sandra; . Kasidi (Hemera Zoa, 2018)
The foot and mouth disease (FMD) is still a major issue in the world of animal health. To date, not many countries are free from FMD; Indonesia is a country that has been FMD-free since 1986 and has been acknowledged by the World Animal Health Organization (OIE) from 1990.  This success was not easily obtained, as a huge amount of energy, funds, and thoughts were expended over a period of nearly one hundred years. The regional situation in Asia at present is still a huge threat to the potential of FMD entry. Malaysia, Thailand, and India are risks for the re-entry of the disease to Indonesia.There are constant efforts to smuggle meat in from regional Asian countries. The eastern coast of Sumatra is still a favorite area for importing meat illegally from countries not yet FMD-free. Moreover, the import of frozen boneless meat from FMD-free zones in India is still a threat and could potentially spread FMD to our country. Therefore, there need to be anticipation efforts and an early detection ability to identify the FMD virus which might be carried by imported meat. The meat that enters illegally and comes from FMD-free zones in India has the potential for bringing and spreading FMD; The lack of a specific method to be used as a tool for detection of FMD through imported or illegal meat.The purpose of this method development activity is to acquire a suitable, quick, and highly accurate method in detection of FMD which might be carried by imported or illegal meat; one of these methods is assessment using Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). This method is expected to become a standard method in FMD testing in the Agricultural Quarantine Agency.